2010
DOI: 10.1111/j.1742-4658.2010.07763.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus nidulansα‐galactosidase of glycoside hydrolase family 36 catalyses the formation of α‐galacto‐oligosaccharides by transglycosylation

Abstract: The a-galactosidase from Aspergillus nidulans (AglC) belongs to a phylogenetic cluster containing eukaryotic a-galactosidases and a-galacto-oligosaccharide synthases of glycoside hydrolase family 36 (GH36). The recombinant AglC, produced in high yield (0.65 gAEL )1 culture) as His-tag fusion in Escherichia coli, catalysed efficient transglycosylation with a-(1 fi 6) regioselectivity from 40 mm 4-nitrophenol a-d-galactopyranoside, melibiose or raffinose, resulting in a 37-74% yield of 4-nitrophenolrespectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 60 publications
2
39
1
1
Order By: Relevance
“…Tetrameric assemblies based on the structure of AgaSK could be constructed for Aga1 and Aga2 and revealed that the active site pocket, similarly to that of Lactobacillus brevis and L. acidophilus NCFM ␣-galactosidases (25), is forged by the tight association of adjacent monomers, suggesting cooperation between subunits, although this needs to be further confirmed. Family GH36 members carry out hydrolysis with a net retention of the anomeric configuration, which is why enzymes from this family have been shown to possess transglycosylation activity (38). This property is essential for the synthesis of oligosaccharide structures which cannot be synthesized by classical chemistry (51).…”
Section: Analysis Of Ruminococcus Gnavus E1 ␣-Galactosidasesmentioning
confidence: 99%
“…Tetrameric assemblies based on the structure of AgaSK could be constructed for Aga1 and Aga2 and revealed that the active site pocket, similarly to that of Lactobacillus brevis and L. acidophilus NCFM ␣-galactosidases (25), is forged by the tight association of adjacent monomers, suggesting cooperation between subunits, although this needs to be further confirmed. Family GH36 members carry out hydrolysis with a net retention of the anomeric configuration, which is why enzymes from this family have been shown to possess transglycosylation activity (38). This property is essential for the synthesis of oligosaccharide structures which cannot be synthesized by classical chemistry (51).…”
Section: Analysis Of Ruminococcus Gnavus E1 ␣-Galactosidasesmentioning
confidence: 99%
“…Family GH36 members originate from bacteria, fungi, and plants and carry out hydrolysis with a net retention of the anomeric configuration, which is why many enzymes from this family have been shown to possess transglycosylation activity (21)(22)(23)(24)(25)(26)(27). For their ability to hydrolyze ␣-galactosides non-digestible by humans and to synthesize diverse oligosaccharides, GH36 ␣-galactosidases have potential applications for the production of prebiotics.…”
mentioning
confidence: 99%
“…Many microorganisms, plants, and animals produce a-galactosidases with multiple subunits [13,27]. Most of the GH family 36 a-galactosidases exist as tetramers with subunit molecular mass of $80 kDa [1,12,14,15]. In this study, RmgalB had a relative molecular mass of 83.1 kDa in SDS-PAGE and a native molecular mass of 317.7 kDa (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Many a-galactosidases from fungi such as Bispora sp. [18], Clostridium josui [26] and Neosartorya fischeri [27] belong to GH family 27 while several a-galactosidases from fungi such as R. miehei [15], Aspergillus nidulans [14], Gibberilla sp. [13], Absidia corymbifera [12] belong to GH family 36.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation